2021
DOI: 10.1021/acsami.1c16263
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the Allometric Growth and Dissolution of Zn Anodes at Initial Nucleation and an Early Stage with Atomic Force Microscopy

Abstract: Zn anodes have gained intensive attention for their environmental-friendliness and high volumetric capacity but are limited by their severe dendrite formation. Understanding the initial nucleation behavior is critical for manipulating the uniform deposition of Zn. Herein, the allometric growth and dissolution of Zn in the initial nucleation and early stages are visualized with in situ atomic force microscopy in aqueous ZnCl2 electrolytes. Zn nuclei grow via a horizontal radial direction and dissolve reversibly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…S8 † ), indicating the good stability of the Zn anode interfaced with the gel electrolyte. 27 The Zn battery delivered a maximum areal energy density of 39 mW h g −1 at a power density of 307 mW g −1 (Fig. S9 † ).…”
Section: Resultsmentioning
confidence: 99%
“…S8 † ), indicating the good stability of the Zn anode interfaced with the gel electrolyte. 27 The Zn battery delivered a maximum areal energy density of 39 mW h g −1 at a power density of 307 mW g −1 (Fig. S9 † ).…”
Section: Resultsmentioning
confidence: 99%
“…It is certain that the symmetric cell with a bare Zn anode presents a larger voltage hysteresis (79.1 mV) ( Supplementary Figure S3A ) and suddenly failed after 45 h cycling. These phenomena may be attributed to the accumulation of side reaction products ( Supplementary Figure S4 ) and the prominent dendrite growth ( Figure 2B ) ( Zhou et al, 2021a ; Zhou et al, 2022c ). By sharp contrast, the TA@Zn|TA@Zn cell exhibits the best electrochemical performance with a prolonged cycling lifespan of over 850 h ( Figure 2D ) with a small voltage hysteresis of 57.8 mV at 1 mA cm −2 , 1 mAh cm −2 , implying that the immersion time of 1 min is the optimal condition for the fabrication of the TA@Zn electrode ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, by in situ surveying the morphology change of Zn at the initial stage of electroplating (Fig. 5 b), it concluded that the Zn deposition could not get rid of the influence of the substrate in a short time [ 62 ].
Fig.
…”
Section: Characterization Techniques Of Seimentioning
confidence: 99%